COVID-19 Amplifiers on Health Inequity Among the Older Populations - Lee, Sora (Frontiers in Public Health, 2021)
The COVID-19 is affecting the population disproportionately and is continuously widening the gap between populations. The disparities are also apparent within the older population. This study highlights how COVID-19 amplifies its impact on health inequity among the older populations. In particular, a number of amplifiers have been identified: 1) expansion of riskscape; 2) reduction of social ties; 3) uncertainty of future; 4) losing trust in institutions; 5) coping with new knowledge; 6) straining on public spending. Based on some of the recent studies on COVID-19 and the older population, the various cascades toward health inequity have been projected. While the fundamental mitigating responses to health inequity among the older population is tackling existing inequalities, this study may help alleviate far-reaching consequences of COVID-19 on the older population by providing policy implications on the identified amplifiers.